Nightmare case of repeated hemorrhagic pancreatitis due to pancreatic head cancer in the acute stage after two-stage lung transplantation - Tatsuya Hayashi; Shin Tanaka; Tsuyoshi Ryuko; Yasuaki Tomioka; Kentaroh Miyoshi; Mikio Okazaki; Seiichiro Sugimoto; Shinichi Toyooka (JHLT Open)
In Japan, due to the shortage of deceased organ donors, the use of two-stage lung transplantation (LTx), specifically sequential single-lung transplants (SSLTs), has been increasing. This approach starts immunosuppressive therapy after the first transplantation, which increases the risk of malignancies. Here, we present a case of fatal perioperative hemorrhagic pancreatitis caused by pancreatic head cancer following SSLTs. This case highlights significant challenges in diagnosis and treatment.